Assessment of Pediatric Chemotherapy-Induced Peripheral Neuropathy Using a New Patient-Reported Outcome Measure: The P-CIN. (March 2021) - Smith, Ellen M. Lavoie; Kuisell, Clare; Kanzawa-Lee, Grace; Bridges, Celia M.; Cho, Youmin; Swets, Jenna; Renbarger, Jamie L.; Gilchrist, Laura S.
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is commonly experienced by children receiving neurotoxic chemotherapy. No validated pediatric CIPN patient-reported outcome (PRO) measures exist.Purpose: To test sensitivity, internal consistency reliability, content and convergent validity, and feasibility of the Pediatric Chemotherapy-Induced Neuropathy (P-CIN), an electronic PRO measure for assessing CIPN in children who received neurotoxic chemotherapy.Method: Five experts evaluated content validity of the 14-item P-CIN. Children 5 to 17 years old with CIPN ( N = 79) completed the P-CIN via tablet computer; a subset ( n = 26) also underwent neurological examinations using the Pediatric–Modified Total Neuropathy Score. Following preliminary analyses, one item was deleted and three others modified. The revised P-CIN was retested with patients ( n = 6) who also completed the Bruininks–Oseretsky Test of Motor Proficiency motor function assessment. Means, item response ranges, standard deviations, content validity indexes, Cronbach's alphas, and correlation coefficients were calculated.Results: Mean participant age was 11.25 ( SD = 4.0) years. Most had acute leukemia (62.5%) and received vincristine (98.7%). Content validity index coefficients ranged from .80 to 1.0 ( p = .05). For 9 of 14 items, responses ranged from 0 to 4 or 5; response ranges for toe numbness, pick up a coin, and three of four pain items were 0 to 3. After deleting one item, Cronbach's alpha coefficient was .83. P-CIN scores were strongly associated with Pediatric-Modified Total Neuropathy Score ( r = .52, p < .01) and Bruininks–Oseretsky Test of Motor Proficiency ( r = −.83, p = .04) scores. Sixty-eight percent of children 6 to 17 years old completed P-CIN independently.Discussion: Preliminary evidence suggests that the 13-item P-CIN is internally consistent, is valid, and can be completed independently by children ≥ 6 years. However, we recommend additional testing.